Deep Peroneal Nerve Injury Following Hardware Removal for Lisfranc Joint Injury. (March 2020) - Meyerkort, Daniel James; Gurel, Ron; Maor, Dror; Calder, James David Forbes
Background: Surgical exposure of the Lisfranc joint complex is within close proximity to the deep peroneal nerve, which can be injured in this approach. Common clinical practice is to remove Lisfranc hardware at 3 to 4 months postoperatively. However, it is unknown if this provides a clinical benefit or risks injury to the deep peroneal nerve. The rate of nerve injury is currently unknown from the published literature. This study clarifies rates of neurological injury to the deep peroneal nerve during primary surgery and hardware removal. Methods: This retrospective study was performed on all patients of a single surgeon from 2012 to 2018. Fixation was performed with locking plates or screws depending on the injury pattern. All patients who required open reduction and internal fixation routinely underwent hardware removal during this time. Neurological injury was assessed in a binary fashion (normal or abnormal) at 2, 6, and 12 weeks after the primary surgery and 2 and 12 weeks after hardware removal. McNemar's test was performed to compare the rates of injury. Patients were contacted at a minimum follow-up of 15 months (range, 15-87 months) to assess persistent nerve injury and satisfaction. Fifty-seven patients with an average age of 29.8 years were included in the final analysis; all had documentation at 3 months postsurgery. Results: All patients had normal neurology before surgery. The rate of nerve injury for the primary surgery (11%) was significantly lower than the rate for patients with nerve injury following hardware removal (23%). However, the rate of spontaneous neurological recovery was low, with symptoms persisting in 5 of 6 patients between the primary operation and subsequent hardware removal. When these patients were excluded from the analysis, the rate of new nerve injury following hardware removal (15%) was not significantly different from the primary surgery rate. Seventy-one percent of nerve injuries persisted at the minimum 15-month final follow-up, with all patients with nerve injury being very or partially satisfied. Conclusion: The rate of deep peroneal nerve injury from primary Lisfranc fixation was 11%, and when routine hardware removal was planned the overall rate of nerve injury rose to 23%. This may be useful information during the patient consent process. Level of Evidence: Level IV, case series.